2007
DOI: 10.1177/0018726707081158
|View full text |Cite
|
Sign up to set email alerts
|

Nobody in charge: Distributed change agency in healthcare

Abstract: This article illustrates how distributed change agency can implement complex organizational changes in the absence of formal management plans, roles, and structures. Distributed change agency typically involves small teams and senior groups. In this qualitative study of service improvements in the treatment of prostate cancer at an acute hospital, Grange, change roles were distributed more widely, with responsibilities `migrating' among a large informal cast supporting four central characters. This distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
174
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(191 citation statements)
references
References 38 publications
15
174
1
1
Order By: Relevance
“…This finding also reflects the intimations of Alexander et al (2001) on the importance of what they call ‗collateral leadership' among both staff and community groups in the community-care networks they study, as a complement to-not a substitute for-more vision-based leadership. Our findings here converge with and develop existing literature in Europe and North America on distributed leadership in health-care settings (Denis et al, 2000;Huxham and Vangen 2000;Buchanan et al 2007a), local government (Hartley and Allison 2000) and education (Leithwood et al 1999;Spillane et al 2001;Gronn 2002). These studies illustrate the importance of subtle, distributed forms of leadership in settings characterized by the ambiguity of objectives and power relationships that typifies public-service organizations, particularly professional bureaucracies.…”
Section: Discussionsupporting
confidence: 89%
“…This finding also reflects the intimations of Alexander et al (2001) on the importance of what they call ‗collateral leadership' among both staff and community groups in the community-care networks they study, as a complement to-not a substitute for-more vision-based leadership. Our findings here converge with and develop existing literature in Europe and North America on distributed leadership in health-care settings (Denis et al, 2000;Huxham and Vangen 2000;Buchanan et al 2007a), local government (Hartley and Allison 2000) and education (Leithwood et al 1999;Spillane et al 2001;Gronn 2002). These studies illustrate the importance of subtle, distributed forms of leadership in settings characterized by the ambiguity of objectives and power relationships that typifies public-service organizations, particularly professional bureaucracies.…”
Section: Discussionsupporting
confidence: 89%
“…On another plane, "Promoting professional cultures that support teamwork, continuous improvement and patient engagement" is seen as essential for high-performing collaborative systems [Baker, (2011a), p.13]. Buchanan et al (2007) found a leadership within the five systems which was both robust as well as distributed and shared (Baker, 2011b). The level of resource and support provided between a broader healthcare system and culture could help, or perhaps also hinder, improvement collaborative.…”
Section: Characteristics Of High-performing Health Systemsmentioning
confidence: 99%
“…Not discounting the cross-terminology of change management, change leadership and change agency (Gill, 2002;Buchanan et al, 2007), healthcare reform and development of more innovative models for improvement are heavily influenced by having the relevant project management systems and capabilities in place (Lannon and Peterson 2013;Øvretveit and Klazinga, 2013). Change management practices are an essential ingredient in the context of healthcare reforms through their main focus on the human resource (Bamford and Daniel, 2005).…”
Section: Characteristics Of High-performing Health Systemsmentioning
confidence: 99%
“…In part, this is due to the distinctiveness of healthcare that makes it difficult to apply generic management knowledge (Buchanan, 2013;Currie & Suhomlinova, 2006). However, it is also due to the highly differentiated nature of healthcare organizations (Hartley & Benington, 2006;Willem & Buelens, 2006) and the distributed nature of their internal management (Buchanan et al, 2007). This shapes managerial practice in complex ways and inhibits the spread of management practices and knowledge.…”
Section: Introduction: Transformations In Healthcare Managementmentioning
confidence: 99%